Ambulatory models for autologous stem-cell transplantation: a systematic review of the health impact - Prieto del Prado, Miguel Ángel; Fernández Avilés, Francesc (Frontiers in Immunology, 2024)
Página 2 de 29 Ambulatory models for ASCT Autologous stem-cell transplantation (ASCT) is the standard of care for the management of multiple myeloma and has a well-established role in the treatment of some types of lymphoma. Over the last decades, the number of ASCT performed has increased significantly, leading to elevated pressure and cost for healthcare services. Conventional model of ASCT includes the admission of patients to a specialized Transplant Unit at any stage of the procedure. To optimize healthcare provision, ambulatory (outpatient/at-home) setting should be the focus moving forward. Thus, ambulatory ASCT model permits reducing average hospital stays and pressures on healthcare services, with significant cost-saving benefits and high degree of patient and caregiver satisfaction. In addition, it facilitates the bed resource for other complex procedures such as allografts or CAR-T cell therapy. The aim of this systematic review is to document the health impact, feasibility and safety of the outpatient/at-home ASCT models, which are increasingly being applied around the world.